Pengaruh Intensitas Pemanfaatan E-Commerce Dan Tingkat Literasi Ekonomi Terhadap Tingkat Konsumsi Siswa Di SMA Negeri 4 Malang - Mona Afiffah Fauziyah; Sri Handayani (Jurnal Pendidikan Ekonomi, 2020)
The level of consumption is how extent the level of consumption is carried out by students. It is because there is a convenience in doing consumption through the famous shopping application that commonly known as Shopee. In this study, the level of consumption is affected by two factors, they are e-commerce utilization intensity as well as the level of economic literacy. The aims of this study are 1) to know the effect of e-commerce utilization intensity on the level of student’s consumption in SMA Negeri 4 Malang 2) to know whether there is an effect of the level of economic literacy on the level of students’ consumption in SMA Negeri 4 Malang 3) to know whether there is an effect of e-commerce utilization intensity and the level of economic literacy on the level of students’ consumption in SMA Negeri 4 Malang. The populations of this conducted study were all students of class X IPS SMAN 4 Malang that consist of 103 students, whereas only took samples of 82 students. The type of this present research is explanatory research in which using multiple linear regression analysis techniques. The results of this study were that e-commerce utilization intensity had a significant effect on the consumption levels of 38.67%. It is because in the industrial revolution 4.0 era, teenagers want to be fast, easy and practical in fulfilling their needs. The level of economic literacy had a significant effect on the consumption levels of 5.80%. Moreover, in the industrial revolution 4.0 era, teenager in fulfilling their needs no longer apply the economic literacy, because e-commerce has provided more convenience in fulfilling the people’s needs. Especially for class X students who were still in basic level understanding of economics, so that they had not been able to apply economic literacy that is included in everyday life. DOI: https://dx.doi.org/10.17977/um014v13i12020p076